Experiment on seagrass (Zostera marina) response to chronically elevated temperature: oxygen in benthocosms - Sawall, Yvonne; Pansch, Christian; Ito, Maysa (In: Sawall, Y et al. (2021): Experiment on seagrass (Zostera marina) response to chronically elevated temperature [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937394, 2021)
This study simulated a 9-months warming scenario on the common seagrass Zostera marina from winter into summer (December 2015 - August 2016) in the Western Baltic Sea (Kiel Fijord), using outdoor mesocosms. Two treatments were applied: Ambient temperature regime (Ambient) and Ambient + 3.6C (Heat) over the entire course of the experiment. Temperature regimes were compared to the 22-year temperature average in the area. This dataset shows concentration of dissolved oxygen per treatment (Ambient, Heat) as the mean and confidence interval (CI) across all benthcosms per treatment (n=6).
Keywords: flowering; Seagrass; Seasonality; Sea surface temperature rise; thermal tolerance; winter warming; Zostera marina